Analisis Pencegahan Kecelakaan Kerja Menggunakan Metode Job Safety Analysis Pada Dinding Penahan Tanah Di Proyek CWP-02 Gedung FPEB UPI - Bundiani, Ninda; Rahayu, Sri (Akademi Komunitas Negeri Aceh Barat, 2023)
Abstract Retaining wall work is a job that has a high risk of work accidents, so it needs special attention to the application of OHS in its implementation. This research focuses on the analysis of occupational accident prevention of Retaining Wall (DPT) worl using the Job Safety Analysis (JSA) method. The JSA method is important in identifying and controlling potential hazards, as well as increasing productivity in reducing lost working hours due to accidents and injuries in the workplace, so you don't have to worry about the targets that have been set. The research was conducted using a qualitative descriptive method with the JSA approach and referring to the security norms ISO: 45001. The results showed that there were 25 types of potential hazards. These potential hazards are significantly more frequently found in stone retaining wall installation work with a total of 11 potential hazards, while a small number of potential hazards are found in embankment work with a total of 5 potential hazards. There are mandatory activities as hazard control in each job including work permit activities before implementation begins, the next step is the implementation of pre-start job meetings/tool box meetings, ensuring work permits have been approved by the authorities, and housekeeping. The recommended hazard control recommendations are carrying out equipment maintenance inspections, operator and equipment inspections, checking the placement and condition of power cables, routine procurement of safety talk, supervision of task implementation and use of Personal Protective Equipment (PPE). Keywords: Retaining Wall; Job Safety Analysis (JSA); Occupational health and Safety.__________________________ Abstrak Pekerjaan Dinding Penahan Tanah (DPT) memiliki risiko kecelakaan kerja yang tinggi, maka perlu perhatian khusus terhadap penerapan K3 dalam pelaksanaannya. Penelitian ini fokus pada analisis pencegahan kecelakaan kerja pada pekerjaan DPT menggunakan metode Job Safety Analysis (JSA). Metode JSA penting dalam mengidentifikasi dan mengendalikan potensi bahaya, serta meningkatkan produktivitas dalam mengurangi kehilangan jam kerja akibat kecelakaan dan cedera di tempat kerja, sehingga tidak perlu khawatir akan target yang telah ditetapkan. Penelitian dilakukan dengan metode deskriptif kualitatif dengan pendekatan JSA serta merujuk kepada norma keamanan ISO:45001. Hasil penelitian menunjukkan bahwa terdapat 25 jenis potensi bahaya. Potensi bahaya tersebut secara signifikan lebih sering ditemukan dalam pekerjaan pemasangan batu dinding penahan dengan jumlah 11 potensi bahaya, sedangkan jumlah potensi bahaya yang sedikit ditemukan dalam pekerjaan timbunan dengan jumlah 5 potensi bahaya. Terdapat kegiatan wajib sebagai pengendalian bahaya pada setiap pekerjaan diantaranya kegiatan perizinan kerja sebelum pelaksaaan dimulai, langkah selanjutnya adalah pelaksanaan pre-start job meeting/tool box meeting, memastikan work permit telah disetujui oleh pihak berwenang, dan housekeeping. Rekomendasi pengendalian bahaya yang diusulkan adalah dilakukannya inspeksi pemeliharaan alat, pemeriksaan operator dan alat, pemeriksaan penempatan dan kondisi kabel listrik, pengadaan safety talk secara rutin, pengawasan pelaksanaan tugas dan penggunaan Alat Pelindung Diri (APD).